The reasonableness among the principles of the law-application process - Мандрикова, К. О. (Theory and practice of jurisprudence, 2016)
The main requirements for the process of law application are described in the article. The author analyzes the principle of reasonableness in the system of law-enforcement. The importance of reasonableness in the common law countries is discussed.